2017
DOI: 10.2136/sssaj2017.03.0101
|View full text |Cite
|
Sign up to set email alerts
|

Decimetric‐Scale Two‐Dimensional Distribution of Soil Phosphorus after 20 Years of Tillage Management and Maintenance Phosphorus Fertilization

Abstract: Improving soil test p assessment at plot scale is essential for productivity in conservation agriculture systems. We characterized the distribution of Mehlich-3 p (p M3 ) concentrations at the decimetric scale with depth on either side of the sowing row in no-till (nT) and moldboard plow ( geostatistical semivariance analysis indicated a predominance of random spatial dependence in most plots, except two plots (one Mp and one nT) with moderate spatial structures. The 2-D geospatial model related to tillage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…Thus, R 2 CV should also be considered as an important reliability factor for mapping soil P indicators in grassland fields to prevent P pollution. Some authors [58] reported lower R 2 CV values (0.0-0.20), while others [20,35] found higher R 2 CV values (0.59-0.62) for soil-available P. In this study, the lowest R 2 CV values obtained may be explained by the weak spatial structure of the soil P obtained, as suggested by Kravchenko [61].…”
Section: Spatial Distribution Of Soil Phosphorus Indices and Other So...supporting
confidence: 42%
See 2 more Smart Citations
“…Thus, R 2 CV should also be considered as an important reliability factor for mapping soil P indicators in grassland fields to prevent P pollution. Some authors [58] reported lower R 2 CV values (0.0-0.20), while others [20,35] found higher R 2 CV values (0.59-0.62) for soil-available P. In this study, the lowest R 2 CV values obtained may be explained by the weak spatial structure of the soil P obtained, as suggested by Kravchenko [61].…”
Section: Spatial Distribution Of Soil Phosphorus Indices and Other So...supporting
confidence: 42%
“…The spatial dependence of soil P indices in both YG and OG soil layers was moderate (31% to 71%) as a result of the interaction between soil intrinsic and extrinsic factors, such as intensive fertilization or farming practices. Many authors [18,20,33,[54][55][56][57][58] have found moderate spatial dependence for soil P, while others [3,19,42,50] have reported strong spatial dependence for soil P (R > 75%) in their respective studies conducted on different scales. The strong spatial dependence of soil-available P observed in these studies may be attributable to the strong influence of intrinsic factors, such as different soil types or soil series, on the spatial distribution of soil-available P at different agricultural, local, or regional scales.…”
Section: Spatial Dependence Of Soil Phosphorus Indices and Other Soil...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies [2,[28][29][30][31][32] have examined the spatial variability of soil P under various tillage systems at different sampling, plot or field scales. Cambouris et al [33] characte-rized the distribution of Mehlich-3 P (P M3 ) concentrations and agri-environmental P saturation (P/Al) M3 at decimetric scale in NT and moldboard plow (MP) plots in a long-term maizesoybean rotation (>20 yr). They observed high CVs associated with P M3 data in both MP (77% and 63% at 0-5 and 5-20 cm, respectively) and NT plots (46% and 66% at 0-5 and 5-20 cm, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, precision agriculture (PA) is defined as a complication of operations and tools to assess farming needs and apply them precisely in the optimal location at the most opportune time [16,17]. This approach involves more precise seeding, fertilizer, irrigation, and pesticide input in order to optimize crop production for the purpose of increasing grower revenue and protecting the environment [18]. The advent of electric-driven control systems has significantly expanded the scope for integrating technological advancements in automation into various PA applications [19,20].…”
Section: Introductionmentioning
confidence: 99%